Land Use Intensification Effects in Soil Arthropod Community of an Entisol in Pernambuco State, Brazil - G. M. Siqueira; E. F. F. Silva; J. Paz-Ferreiro (The Scientific World Journal)
The interactions between soil invertebrates and land use and management are fundamental for soil quality assessment but remain largely unaddressed. The aim of this study was to evaluate the changes in soil arthropod community of an entisol brought about by different land use systems under semiarid climate in Pernambuco State, Brazil. The soil invertebrate community was sampled using pitfall traps from areas with eight vegetation types by the end of the austral winter. The land uses studied were native thorn forest plus seven agricultural fields planted with elephant grass, apple guava, passion fruit, carrot, maize, tomato, and green pepper. Native vegetation was considered as a reference, whereas the agricultural fields showed a range of soil use intensities. The abundance of organisms, the total and average richness, Shannon’s diversity index, and the Pielou uniformity index were determined, and all of these were affected by several crop and soil management practices such as residue cover, weed control, and pesticide application. Our study found differences in community assemblages and composition under different land use systems, but no single taxa could be used as indicator of soil use intensity.